CLINICAL MENTORING THE VIEWS OF THE NURSING STUDENTS AND CLINICAL MENTORS - Mthembu, Sindi (Journal of Community and Health Sciences, 2020)
In nursing, clinical learning is an important part of the curriculum and accounts for approximately 50% of the pre-registration nursing programme. Supporting students to learn in clinical settings is an important function for both educators and practitioners, however, there is little consensus in the literature on what constitutes appropriate learning support. This study was aimed at exploring the phenomenon of clinical mentoring as perceived by the nursing students and clinical mentors in a selected hospital in Durban. Aqualitative descriptive approach was used in this study with a population of 48 registered nurses and 47 nursing students who were doing the four-year diploma in nursing. Sample size consisted of eight registered nurses and eight student nurses. Individual interviews were conducted to collect data. The findings revealed that the assistance and guidance that the clinical mentors are offering to students are most crucial for growth and the development of students and gain of quality clinical skills. Challenges to the mentoring process included time constraints, shortages of human and material resources in the clinical facilities and lack of a system in place for the preparation of clinical mentors for this role. This study suggests that the educational and clinical settings needs to work together to ensure that formalised mentorship programmes are put in place where clinical mentors will be trained for the role and formally appointed to the roles.